A novel methodology for dynamic response maximisation in multi-axis accelerated random fatigue testing. (1st December 2022) - D'Elia, Giacomo; Mucchi, Emiliano; Dalpiaz, Giorgio
Abstract: This paper investigates the effects caused by simultaneous multiple random excitations on the fatigue-life of the specimen under test. In multi-axis accelerated fatigue testing, the test specifications are usually provided in terms of PSDs only. However, different combinations of the test specifications can significantly affect the fatigue behaviour of the specimen, resulting in altered failure modes and test durations. In this context, the original contribution of this paper is to provide a novel method for combining the PSD test specifications, which is able to recreate in the laboratory the most severe and damaging vibration environment possible. The aim of the present methodology is to get out the extreme dynamic response of the specimen by fully exploiting the total energy offered by the test specifications. This method avoids the risk of underestimating the fatigue damage to undergo the specimen during laboratory testing. The paper offers the mathematical implementation of the method and its experimental validation achieved throughout an intense test campaign. Fatigue tests have been performed on specially designed specimens, by exploiting a three-axial electro-dynamic shaker.